Echocardiographic Assessment of Right Ventricular Function Before and After Surgery in Patients with Pectus Excavatum and Right Ventricular Compression - Gürkan, Ufuk; Aydemir, Bülent; Aksoy, Sukru; Akgöz, Haldun; Tosu, Aydın Rodi; Öz, Dilaver; Güngör, Barış; Yılmaz, Hale; Bolca, Osman (The Thoracic and Cardiovascular Surgeon, 2014)
Background We aimed to evaluate the effect of surgical repair on right ventricular (RV) function in patients with pectus excavatum (PE) and RV compression by Doppler echocardiography.Materials and Methods Twenty-three patients who were admitted to our hospital for surgical correction of PE between 2009 and 2012 were included in the study. After transthoracic echocardiographic evaluation, 16 patients with RV compression were enrolled. All patients were males (100%) with a mean age of 20.5 ± 5.6 years. Transthoracic echocardiography was repeated 1 month after surgery. Echocardiographic evaluation included the assessment of RV diastolic diameter, tricuspid annular plane systolic excursion (TAPSE), pulsed tissue Doppler systolic velocity (S′), RV isovolumic acceleration (RV IVA), systolic pulmonary artery pressure, left ventricular (LV) ejection fraction, and myocardial performance indexes of both the right and the left ventricles (Tei index).Results Following the surgery, the RV end-diastolic diameter, TAPSE, S′, and RV IVA were found to be significantly increased in patients with PE. In addition, RV and LV Tei index significantly improved after surgical correction.Conclusions RV function significantly improved after corrective surgery. Quantitative echocardiographic examination provides accurate estimation when deciding for corrective surgery and also should be used in the assessment of postoperative improvement.
Keywords: pectus excavatum; surgical correction; echocardiography; right ventricular function